1998
DOI: 10.1128/iai.66.4.1408-1412.1998
|View full text |Cite
|
Sign up to set email alerts
|

Elastase Is the Only Human Neutrophil Granule Protein That Alone Is Responsible for In Vitro Killing of Borrelia burgdorferi

Abstract: Phagocytosis of Borrelia burgdorferi by human polymorphonuclear leukocytes triggers oxygen-dependent and -independent mechanisms of potentially cidal outcome. Nevertheless, no factor or process has yet been singled out as being borreliacidal. We have studied the B. burgdorferi-killing ability of the myeloperoxidase-H2O2-chloride system and that of primary and secondary granule components in an in vitro assay. We found that neither secondary granule acid extracts nor the chlorinating system could kill these mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Intracellular seprocidin activity is required for killing of bacteria within the neutrophil 3 , 17 19 . Based on the propensity of dendrimeric scaffolds to carry cargoes into cells 20 , 21 , the intracellular visualisation of serprocidin activity was explored.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular seprocidin activity is required for killing of bacteria within the neutrophil 3 , 17 19 . Based on the propensity of dendrimeric scaffolds to carry cargoes into cells 20 , 21 , the intracellular visualisation of serprocidin activity was explored.…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, the augmented killing is not compromised by heat‐inactivating HNE enzymatic activity, suggesting that elastolytic action is not a prerequisite for synergy. The independence of anti‐microbial action from enzymatic activity has been observed in studies of PMN– Borrelia interactions (72) and applies to other serprocidins, including cathepsin G (33, 73). Given the cationic nature common to this group of granule proteins, it is reasonable to speculate that their strong electrostatic interactions with the microbial surface disrupt the integrity of the organism, rendering potential targets more accessible to attack.…”
Section: Cooperation Among Anti‐microbial Agents Within the Pmnmentioning
confidence: 90%
“…Elastase has a death function separable from and independent of its proteolytic activity. 43 It has recently been shown that azurocidin is internalized into endothelial cells and is targeted to mitochondrial compartments of the cell, but not in the nuclear compartment. 44 Interestingly, internalized azurocidin markedly reduces growth factor deprivation-induced apoptosis, and the authors have suggested that uptake of exogenous azurocidin contributes to the sustained viability of endothelial cells in the context of locally activated neutrophils.…”
Section: Discussionmentioning
confidence: 99%